Beyond Religion in India and Pakistan: Gender and Caste, Borders and Boundaries - Purewal, Navtej Kaur (Bloomsbury Studies in Religion, Gender, and Sexuality, 2019)
1 Introduction; 2 Conceptual pilgrimage; 3 Bordering logics; 4 Sacred spaces and their limits; 5 Openness and closure; 6 Authority as religion-making and religion-breaking; 7 Devotion, hegemony and resistance at the margins